(untitled) (Nigerian Journal of Technology, 2018)
Selected Jute fiber reinforced composites sacks locally used for cassava pulp dewatering were subjected to dewatering pressure tests to ascertain their average maximum dewatering pressure bearing capacity. Existing hydraulic jack was modified for the purpose of the experiment at Divine engineering works Owerri. In the course of this study, fifteen independent trials were performed. The summary of the results show that, the maximum breaking pressures of 152.068kN/m2, 160.632kN/m2, and 174.465kN/m2 at 10kg, 15kg and 20kg respectively of the product were recorded. These maximum sack breaking pressure values were observed for all product quantities when the Jute fiber reinforced composites sack for Rice packaging was used. It is therefore recommended that improved jute fiber reinforced composites popularly used for bagging rice products be use for the dewatering operations of cassava pulp especially where high dewatering pressure is required. http://dx.doi.org/10.4314/njt.v37i3.31